Notary Public Liability for Errors in Authentic Deeds from the Perspective of Article 16 of the Notary Office Act - Nurain Husain (SEAN Institute, 2026)
This study examines notarial liability for errors in authentic deeds from the perspective of Article 16 of the Notary Office Act within the Indonesian civil law system. Employing a normative juridical research method, the study integrates statutory analysis, doctrinal review, and a purposive examination of Supreme Court decisions to analyze the configuration of notarial liability and its practical implications. The findings demonstrate that notarial liability operates within a tiered and progressive framework encompassing civil, administrative, and criminal liability, with civil liability emerging as the dominant form of accountability, particularly in cases involving substantive errors. The study further classifies notarial errors into formal errors, substantive errors, and negligence in digital verification, revealing that digitalization has expanded the scope and complexity of the professional duty of due care. Although the normative framework governing notarial responsibility is conceptually coherent, its implementation remains uneven due to weaknesses in supervision, digital competence, and risk mitigation mechanisms. Accordingly, the study underscores the need for a systemic and preventive approach to the application of Article 16, aimed at strengthening legal certainty, professional integrity, and public trust in the notarial profession in the digital era.